1997
DOI: 10.1021/bk-1997-0676.ch022
|View full text |Cite
|
Sign up to set email alerts
|

Cold Denaturation of Proteins

Abstract: By taking advantage of the phase behavior of water, high pressure can significantly lower the freezing point of an aqueous protein solution. In this way, using high-resolution, high-pressure NMR techniques, one can investigate not only pressure denaturation but also cold denaturation of proteins.After an overview of compression effects on dynamic and hydrodynamic behavior of water and heavy water at subzero temperatures, the main part of this contribution is devoted to selected results from recent pressure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…We find that above the pressure where water freezes to the dense ice phase (≈ 2 kbar), the mechanism for cold denaturation with decreasing temperature is the loss of local low-density water structure. We find our results in agreement with data of bovine pancreatic ribonuclease A.Some proteins become thermodynamically unstable at low temperatures, a phenomenon called cold denaturation [1,2,3]. This phenomenon has been mainly observed at high pressures, ranging from approximately 200 MPa up to 700 MPa [4].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…We find that above the pressure where water freezes to the dense ice phase (≈ 2 kbar), the mechanism for cold denaturation with decreasing temperature is the loss of local low-density water structure. We find our results in agreement with data of bovine pancreatic ribonuclease A.Some proteins become thermodynamically unstable at low temperatures, a phenomenon called cold denaturation [1,2,3]. This phenomenon has been mainly observed at high pressures, ranging from approximately 200 MPa up to 700 MPa [4].…”
supporting
confidence: 90%
“…Some proteins become thermodynamically unstable at low temperatures, a phenomenon called cold denaturation [1,2,3]. This phenomenon has been mainly observed at high pressures, ranging from approximately 200 MPa up to 700 MPa [4].…”
mentioning
confidence: 99%
“…The decreasing photochemical activity of PSII results from oxygen-evolving complex inactivation of PSII, structural changes in the thylakoid membranes [ 45 ], decreasing of the PSII-mediated electronic transfer rate, and changes of the antenna system conformation by high temperature. On the other hand, cyanobacteria increase the separation between the PBS supermolecules and the thylakoid membrane, which further prompts the disintegration of PBS supermolecules [ 46 ]. The expression level of linking polypeptides CpcC and CpcG significantly increased when compared to the control, which demonstrated that ASP took control measures to prevent phycobilisomes from dissociation due to high or low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…At low temperatures and high pressures (ranging from approximately 200 MPa up to 700 MPa) some proteins become thermodynamically unstable by means of a phenomenon known as cold denaturation [1][2][3][4][5]. An explanation of the P-T phase diagram of a protein with cold denaturation has been proposed [6][7][8], but a microscopic understanding of the mechanisms leading to cold denaturation has yet to be developed, due in part to the complexity of protein-solvent interactions.…”
Section: Introductionmentioning
confidence: 99%